The career destination of doctors who graduated from a medical college in Goa, India between 2000-2005: A retrospective cohort study - Kamat, Umesh S; Ferreira, AMA (South East Asia Journal of Public Health, 2014)
The problem of health manpower shortage in developing countries appears to arise from brain drain or poor inclina-tion of qualified medicos towards medical practice. This study was conducted among the alumni of an allopathic medical college in Goa to find out the proportion of Goan doctors who remain allied to the medical field 5 years after graduating, and to examine the extent of brain drain among these doctors. The doctors who graduated between the years 2000-2005 were contacted through email/telephone/residential address to obtain the relevant information. Of the 383 doctors who graduated during the reference period, 96.6% could be traced, and out of these, 166 were male and 204 were female. The proportion of non-practicing doctors is 23.5%, and as many as 41% of the female medical graduates are not currently in medical profession. All the non-practicing female doctors were married, 52.9% (46/87) settled abroad and 31% (27/87) settled out of Goa. More than 41% of medically affiliated doctors worked out of Goa. Among those working in Goa 50.6% (84/166) worked for government health services, 31.9% (53/166) were attached to a private hospital/clinic, and 17.5% (29/166) were academically affiliated. None of the practicing doctors do general practice on their own. Given the steadily increasing number of female medical gradu-ates who constitute the bulk of non-practicing doctors it is imperative to bring in legislation stating minimum years of medical practice for every medical graduate. The brain drain of nearly 50% is an issue of concern, as also is the reduced number of doctors engaged in general practice. South East Asia Journal of Public Health 2013; 3(1): 65-68 DOI: http://dx.doi.org/10.3329/seajph.v3i1.17714